Program for the Empowerment of Elderly Cadres in Hypertension Management through Physical Activity in the Work Area of the Rancamayar Health Center - Anggriyana Tri Widianti; Nina Gartika (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
According to the World Health Organization (WHO), approximately 1.13 billion people worldwide have hypertension. Hypertensive patients have numerous complications that can result in disability or death. To avoid hypertension, the community needs to be educated on how to live a healthy lifestyle. Cadres from Elderly Integrated Health Centers have the potential to actively promote and prevent hypertension, heart, and blood vessel disease in the community. It is necessary to involve the elderly Integrated Health Centre cadres in improving the level of public health. The Elderly Cadre Empowerment Program in Hypertension Management through Physical Activity seeks to improve the knowledge and skills of the elderly Integrated Health Centre administrators in promoting healthy lifestyles and preventing Hypertension, Heart, and Blood Vessel Disease. This community service activity is conducted through training that includes lectures, two-way discussions, and a 20-minute brisk walking session, followed by assignments in the field. Participants included 23 elderly Integrated Health Centre cadres and Rancamanyar residents. Activities completed three times in one month. This series of assistance includes providing assistance such as hypertension education and brisk walking, fast walking demonstrations, and participating in a 20-minute brisk walk with the community. The achievement of increasing participants' knowledge of hypertension and brisk walking can be said to be good based on the evaluation, and the community can do a 20-minute brisk walk according to the procedure.